Coach education in volleyball: a study in five countries - Resendre, R.; Sarmento, H.; Falcao, W.; Mesquita, I.; Fernandez, J. (Journal of Physical Education and Sport, 2014)
Coach education is a theme of great interest for research because its practice is often not theory driven. The increasing movements for coach professionalization and the need to deepen education and qualifications justify the need for greater theoretical support of the coaching processes. The purpose of this study was to examine the structure of volleyball coach education courses in countries with different levels of development in sport (i.e., Portugal, Spain, Brazil, Italy and France). The sample comprised the documents that regulate volleyball coach education in the five countries under study. Content analysis of the documents revealed some uniformity between the countries, with the exception of France. The analyzed courses focused on performance, revealing a education continuum which evolved from the first until the last level. French courses differ from the other by having more elaborate education proposals, which answered to coaches` needs and distinguishing between participation-oriented and performance-oriented participation.